Experimental yellow fever virus infection in the squirrel monkey (Saimiri spp.) I: gross anatomical and histopathological findings in organs at necropsy - Milene Silveira Ferreira; Pedro Soares Bezerra Júnior; Valíria Duarte Cerqueira; Gabriela Riet Correa Rivero; Carlos Alberto Oliveira Júnior; Paulo Henrique Gomes Castro; Gilmara Abreu da Silva; Wellington Bandeira da Silva; Aline Amaral Imbeloni; Jorge Rodrigues Sousa; Ana Paula Sousa Araújo; Franko de Arruda e Silva; et al. (Memorias do Instituto Oswaldo Cruz, 2020)
BACKGROUND Non-human primates contribute to the spread of the yellow fever virus (YFV) and the establishment of transmission cycles in endemic areas. OBJECTIVE To describe the severe histopathological aspects of YFV infection, 10 squirrel monkeys were infected with YFV and blood, brain, liver, kidney, spleen, heart, lung, lymph node and stomach were collected at 1-7, 10, 20 and 30 days post-infection (dpi). METHODS Histopathological analysis and detection of the genome and viral antigens and neutralising antibodies were performed by RT-PCR, immunohistochemistry and neutralisation test, respectively. FINDINGS Only one animal died from the experimental infection. The genome and viral antigens were detected in all investigated organs (1-30 dpi) and the neutralising antibodies from seven to 30 dpi. The brain contained perivascular haemorrhage (6 dpi); in the liver, midzonal haemorrhage and lytic necrosis (6 dpi) were observed. The kidney had bleeding in the Bowman’s capsule and tubular necrosis (6 dpi). Pyknotic lymphocytes were observed in the spleen (1-20 dpi), the lung had haemorrhage (2-6 dpi), in the endocardium it contained nuclear pyknosis and necrosis (2-3 dpi) and the stomach contained blood in the lumen (6 dpi). MAIN FINDINGS Squirrel monkeys reliably reproduced the responses observed in human cases of yellow fever and, therefore, constitute an excellent experimental model for studies on the pathophysiology of the disease.